1971
DOI: 10.1111/j.1365-2621.1971.tb01592.x
|View full text |Cite
|
Sign up to set email alerts
|

Protein quality and quantity: A rheological assessment of their relative importance in breadmaking

Abstract: It is suggested that the terms 'strong' and 'weak' derived from bakery experience may not always be directly applicable to the quality of gluten present in such fours, and may be more related to gluten quantity than hitherto believed. It is clearly demonstrated in this work that the quality of glutens derived from 'strong' and 'weak' flours may be similar, although the glutens may be present in dissimilar quantity. There are, of course, certain flours which have poor glutens but until these are detected by pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1972
1972
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…However, it is reported that wheat having higher protein contents ([12 %) was also found suitable for chapatti making, indicating the importance of quality or nature of proteins present in wheat in determining chapatti making quality [15]. Considerable amount of work has been reported with regard to protein and gluten contents, the proportion of gluten proteins, high molecular weight glutenin subunit composition and their relation to bread quality [16][17][18][19]. Fractionation and recombination studies have been reported with respect to bread to establish the role of individual constituents on bread quality and similar studies are required for chapattis.…”
Section: Introductionmentioning
confidence: 96%
“…However, it is reported that wheat having higher protein contents ([12 %) was also found suitable for chapatti making, indicating the importance of quality or nature of proteins present in wheat in determining chapatti making quality [15]. Considerable amount of work has been reported with regard to protein and gluten contents, the proportion of gluten proteins, high molecular weight glutenin subunit composition and their relation to bread quality [16][17][18][19]. Fractionation and recombination studies have been reported with respect to bread to establish the role of individual constituents on bread quality and similar studies are required for chapattis.…”
Section: Introductionmentioning
confidence: 96%